2021
DOI: 10.1002/cpe.6269
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of emotion based on audio‐visual stimuli understanding and personalized regulation with concurrency

Abstract: The target of Emotion modeling is to establish an system that can perceive, recognize, and express emotions with concurrency which humanity have by proper mathematical models. A big challenge in Emotion modeling is to establish the complex personal system of an intelligent agent or machine in a quasi‐physical and quasi‐sociological way, so that it rationally responds to emotions and behaviors by different internal and external stimuli with concurrency. For this purpose, an emotion classification model is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Researchers have identified significant variations in physiological measures during music listening, including elements such as melody, rhythm, and continuity [15]. This aligns with Kim and André's findings and is corroborated by other research highlighting music's impact on ANS reactions [16].Notably, certain studies have delved into clinical and therapeutic contexts, uncovering the influence of music on ANS responses [17]. For instance, research has shown that music can trigger ANS reactions such as vascular constriction, heart rate fluctuations, muscle tension, and changes in skin temperature (SKT), even when subjects report reduced anxiety and increased relaxation [18].…”
Section: Introductionsupporting
confidence: 75%
“…Researchers have identified significant variations in physiological measures during music listening, including elements such as melody, rhythm, and continuity [15]. This aligns with Kim and André's findings and is corroborated by other research highlighting music's impact on ANS reactions [16].Notably, certain studies have delved into clinical and therapeutic contexts, uncovering the influence of music on ANS responses [17]. For instance, research has shown that music can trigger ANS reactions such as vascular constriction, heart rate fluctuations, muscle tension, and changes in skin temperature (SKT), even when subjects report reduced anxiety and increased relaxation [18].…”
Section: Introductionsupporting
confidence: 75%